Ten‐year outcome results of cT4 breast cancer after neoadjuvant treatment. Issue 8 (1st September 2021) - Corso, Giovanni; Kahler‐Ribeiro‐Fontana, Sabrina; Pagan, Eleonora; Bagnardi, Vincenzo; Magnoni, Francesca; Munzone, Elisabetta; Bottiglieri, Luca; Veronesi, Paolo; Galimberti, Viviana
Abstract: Background and Objectives: cT4 breast cancer (BC) is classified as noninflammatory breast cancer (non‐IBC) or inflammatory breast cancer (IBC). The outcome often is considered worse. The purpose of this study was to determine recurrence and outcomes in overall survival (OS), invasive disease‐free survival (IDFS), distant disease‐free survival (DDFS) according to pathological complete response (pCR), and inflammatory status. Methods: From 2000 to 2015 we selected 634 nonmetastatic cT4 BC patients treated with neoadjuvant therapy followed by surgery at the European Institute of Oncology. OS, IDFS, and DDFS were estimated with the Kaplan–Meier method. Results: The median follow‐up was 9.0 years. Twenty patients underwent only sentinel node biopsy (SNB), 13 SNB + AD, and 601 only AD. Considering the 614 patients with AD, only 2.5% of non‐IBC patients reported pCR compared to 15% of IBC cases. Only two axillary recurrences were reported. Ten‐year results were 52.3% (95% confidence interval [CI]: 47.8–56.5) for OS, 37.0% (95% CI: 32.6–41.3) for IDFS, and 49.8% (95% CI: 45.0–54.4) for DDFS. OS, IDFS, and DDFS were better in all BC with pCR (irrespective of inflammatory status). Conclusion: Our long‐term results demonstrated that pCR significantly improves survival, reducing locoregional and distant recurrence risk in cT4 tumors with respect to patients with no pCR and according to inflammatory status of cT4 BC.